Issues and challenges in providing quality ICT infrastructure service delivery in a university campus environment - Mohd. Nor, Sulaiman (2008)
Within a university environment, Information and Communication Technology (ICT) has become an important enabler in disseminating and sharing of knowledge through teaching, learning, research and supporting services to the core business. Thus, in this era, it is important that the body responsible for delivering the ICT services within a university campus reorientate the mode of delivery to that of a service provider. Based on this, the Centre for ICT (CICT) at the Universiti of Teknologi Malaysia sets the goal to achieve level three within the IT Management Process Maturity Model (Gartner Research, 2004). In this level, the IT organisation is supposed to define the service classes, the price associated with each classes and how to guarantee the service level as agreed upon. Traditional ICT service delivery is very much reactive and chaotic in nature. To migrate to this level, three tightly coupled components and issues, which relate to these components need to be addressed properly. The three components are technology, processes and people. How the three components relate to the ICT infrastructure strategic map and what are the issues and challenges will be deliberated and discussed in this paper.